Influence of a suspended aid on the hip moment profiles during circles on pommel horse - Fujihara, T.; Gervais, P. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Because a suspended aid - a usual training aid for practicing circles on pommel horse - applies forces at the distal part of the legs, we hypothesized that it has a large influence on the hip moment profiles during circles. This study was conducted to test the hypothesis. Eighteen gymnasts performed three sets of 10 circles with and without a suspended aid, and 3-D coordinates were acquired using a Qualisys motion capture system. The force applied from the aid was determined based on the cable tension measured with a load transducer. Hip joint moments were computed with the assumption that the total leg was a single rigid body. The results confirmed that the aid altered the hip flexion-extension and lateral flexion-extension moments. Understanding such an influence will be important whenever a suspended aid is used for training.